DISTRIBUTION CHARACTERISTICS, BIOACCUMULATION, AND SOURCES OF MERCURY IN RICE AT NANSI LAKE AREA, SHANDONG PROVINCE, CHINA - H. Liu; L. H. Wang; J. Zhang; G. X. Li; J.L. Dai (Journal of Animal and Plant Sciences, 2015)
Mercury (Hg) concentration in rice plant in Nansi Lake area, and rice growing environment was evaluated to elucidate the distribution characteristics, bioaccumulation, and sources of Hg. Results showed Hg distribution in rice followed the order: leaf > root > hull > bran > stem > brown rice > polished rice. Rice bran contained higher Hg concentration than in polished rice (P < 0.05). Bioaccumulation factors for Hg in rice ranged from 0.013 to 3.34, and 17.24% of root, 3.44% of the hull, 6.89% of the bran, 55.17% of the leaf exceeded 1. Principal components analysis indicated among these four growing factors (paddy soil, irrigation, atmospheric deposition and fertilizer), Hg concentrations in fertilizer played the most important role. Hg in atmospheric deposition could serve as the main controlling factor of rice leaf, Hg in paddy soils was the main factor of rice bran, root and stem, whereas, Hg in fertilizer was the main controlling factors of polished rice. Moreover, rice genotype had a certain effect on Hg accumulation of rice. The quality of polished rice in Nansi Lake area was safe, however, bran-made production consumption should be paid attention.
Keywords: Food safety; irrigation water; mercury; paddy soil; pollution distribution; rice